Os estudos etnográficos no Instituto Histórico e Geográfico Brasileiro no início do Século XX - Souza, Breno Sabino Leite de [UNESP] (2015)
This thesis has as objective the analysis of the ethnographic studies in the Instituto Histórico e Geográfico Brasileiro at the beginning of the century XX. Leaving of a mapping of the magazine of the IHGB - its main publication - and of a series of enterprises organized for its partners - I Congresso de História Nacional, I Congresso Internacional de História da América e o Dicionário Histórico, Geográfico e Etnográfico do Brasil - we look for to evaluate the panorama of such studies in the period. The concerns that had guided the research had been in a first plan regarding the subjects and authors who had approached the question, as well as its relation with other areas of the knowledge, especially history. In a second moment, our concern focused on the forms that this etnography could assume, either as trip, linguistics or biological concern. In summary, this thesis intends to act in the crossroads between history of the historiography and history of the anthropology to reflect on the on relation of these disciplines that had had its development inextricably linked for a long period